Optimization of Reduced Fat Mayonnaise by Using Apple Peel Flour as a Stabilizer - Herly Evanuarini; Agus Susilo (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2021)
Reduced fat mayonnaise products have an unstability of the emulsion, so a stabilizer is needed to improve quality of mayonnaise. Apple peel flour can be used as a stabilizer to improve the quality of mayonnaise. The materials used in this study were vegetable oil, egg yolk, vinegar, apple peel flour and other optional ingredients. The research treatment was without the addition of apple peel flour as a control, the use of 1%, 2% and 3% apple peel flour. The objective of this research was to determine the best percentage of apple peel flour as a stabilizer in reduced fat mayonnaise. The research method used is a laboratory experiment method. The design used was a completely randomized design with 4 treatments and 4 replications. Analysis of variance was used to analyze the resulting data, if there was a difference in the effect, it was continued with Duncan's Multiple Range Test.This study resulted that the use of apple peel flour used as a stabilizer resulted gave highly significant difference in reduced fat mayonnaise. The average acidity is 0.66-0.90, the emulsion stability is 96.92- 99.18%, the antioxidant activity is 8.37-19.38%, the carbohydrate content is 2.63-5.81% and ash by 1.72-1.92%. It could be concluded that the use of 3% apple peel flour can produce the best quality reduced fat mayonnaise product and is close to the characteristics of full fat mayonnaise.